2021
DOI: 10.4103/ijo.ijo_2614_20
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment of diabetic macular edema on visual impairment in people with diabetes mellitus in India

Abstract: Purpose: The aim of this study was to report visual and anatomical outcomes following treatment for diabetic macular edema (DME) in clinical practice in India. Methods: Retrospective chart review of patients with DME who were initiated on treatment and followed up for at least 1 year at 9 tertiary eye care centers during 2016–2017 was performed. Data on demographics, systemic illnesses, visual acuity and anatomical characteristics of DME, treatment history were collated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…This finding is comparable to the study by Rajalaxmi et al ( 14), who reported a prevalence of 12.7% in a similar cohort of patients diagnosed with diabetes at a young age. In a recently published article by Kulkarni et al (15), the prevalence of treatable DME was only 3.1% in a cohort of patients >40 years of age with diabetes. Thus, the prevalence of DME and the need for treatment of DME are higher in young people with diabetes compared with older people with diabetes.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is comparable to the study by Rajalaxmi et al ( 14), who reported a prevalence of 12.7% in a similar cohort of patients diagnosed with diabetes at a young age. In a recently published article by Kulkarni et al (15), the prevalence of treatable DME was only 3.1% in a cohort of patients >40 years of age with diabetes. Thus, the prevalence of DME and the need for treatment of DME are higher in young people with diabetes compared with older people with diabetes.…”
Section: Discussionmentioning
confidence: 94%
“…A study in Malaysia suggested an 18.8% prevalence of diabetes associated falls among the elderly. [14] Persons with type 2 diabetes are at increased risk of falling compared to similar aged healthy adults. A combination of diabetes and age (>65 years) increases the risk of falling 17fold.…”
Section: Gcs: Geriatric Conditionsmentioning
confidence: 99%
“…Recent studies have proven that around seven anti‐VEGF injections should be taken per year for desirable results 8 . With an estimated cost of the cheapest anti‐VEGF injection of INR 7000, the expenses can be as high as INR 42000 to 70 000 (USD 575–1000) per year 9 . Patients who undergo anti‐VEGF treatment must be monitored regularly to track the effectiveness, thus making the treatment very expensive.…”
Section: Introductionmentioning
confidence: 99%